Forced Migration, Social Cohesion and Conflict : The 2015 Refugee Inflow in Germany - Albarosa, Emanuele; Elsner, Benjamin (World Bank, Washington, DC, 2022)
In 2015, Germany welcomed close to one million asylum seekers and refugees from Syria, Afghanistan, the Western Balkans and elsewhere. Although the country was often praised for its welcome culture, the inflow has spurred a debate about identity, social cohesion and the limits of multiculturalism. This paper analyzes the effect of this inflow on various dimensions of social cohesion. To separate causation from correlation, it exploits the fact that asylum seekers in Germany are allocated to local areas based on an area’s tax revenues and population several years prior. Therefore, the allocation is unrelated to current economic, political or social conditions. Based on survey data as well as data scraped from newspapers, the paper documents two sets of results. First, it finds no effect on self-reported indicators of trust and perceived fairness, and a small negative effect on and attitudes towards immigrants. In contrast, it finds that the refugee inflow led to an increased incidence of anti-immigrant violence that lasted for about two years. This increase is larger in areas with higher unemployment and greater support for right-wing parties.